Development of a brief screening instrument for emotional distress associated with thromboembolism - Keith S. Keddington; Aubrey E. Jones; Michael Feehan; Daniel M. Witt (Thrombosis Update, 2020)
Background: Venous thromboembolism (VTE) is associated with emotional distress, including depression, anxiety, fear, and decreased quality of life. A method to rapidly screen patients at increased risk for VTE-related emotional distress could allow providers to facilitate appropriate interventions. Objective: To develop a short, easily administered screening tool that can reliably identify emotional distress in patients recently diagnosed with VTE. Methods: An analysis was performed on data from a national online survey of adult patients with recent VTE. The survey included eight questions developed to assess VTE-related emotional distress, as well as the validated Hospital Anxiety and Depression Scale (HADS). Psychometric analysis was used to evaluate our emotional distress questions for internal consistency and determine associations with HADS Anxiety and Depression subscale scores. Results: A total of 907 surveys were included. Factor analysis of the proposed eight questions identified a single factor with an eigenvalue of 5.42. There was a significant and strong correlation with the HADS Anxiety (HADS-A) and HADS Depression (HADS-D) subscale scores, r ​= ​0.71 and r ​= ​0.57, respectively (both p-values <0.001). A total score of 10 or more using our new emotional distress screening tool correlated with HADS-A and HADS-D scores ≥11 indicating high anxiety and/or depression. Conclusions: We developed and tested a new brief screening tool composed of eight questions that assesses patients for VTE-related emotional distress and is easily administered in a clinical setting. Additional investigations in broader populations and in validation studies are required to confirm these findings and foster the tool’s routine use in clinical practice.